EVALUATION OF THE FUNCTIONAL STATE AND FEATURES OF LEFT VENTRICULAR REMODELING IN PATIENTS WITH ACUTE RHEUMATIC FEVER - Safarova, Kh.I. (World of Medicine and Biology, 2022)
The purpose of the study was to identify the features of hemodynamics and structural changes in patients with history of acute rheumatic fever, with and without myxomatous degeneration of the valvular-chordal apparatus. The study included 27 patients aged 15–21 years who had a history of acute rheumatic fever. All patients were divided into 2 groups: group I – patients without myxomatous degeneration; group II – patients with signs of myxomatous degeneration. The comparison group consisted of 14 practically healthy individuals of the appropriate age without a “rheumatic” history and echocardiographic signs of damage to the valvular-chordal apparatus. In patients who had history of acute rheumatic fever, an increase of end-diastolic diameter (by 4.8 %; p